Electromagnetic shielding measurement of equipment casing - Yap, Venus Yu Ying (2018)
Electromagnetic Compatibility (EMC) is of increasing importance as the number of wireless devices increases. However, it is becoming more difficult to meet EMC standards for electronic products that are smaller in size and have faster switching speeds without a well-designed shielding enclosure. Electronics design engineer have to take into account the ventilation design requirement while maintaining the shielding effectiveness (SE) of the enclosure. The metallic enclosure acts as a shield to limit Electromagnetic Interference (EMI) by attenuating radiated emissions from the radiation source housed in the enclosure. Hence, it is important to estimate the SE of the enclosure before fabrication to ensure optimum shielding.